The histamine H4 receptor is a potent inhibitor of adhesion‐dependent degranulation in human neutrophils. Issue 3 (5th May 2014) - Dib, Karim; Perecko, Tomas; Jenei, Veronika; McFarlane, Cheryl; Comer, David; Brown, Vanessa; Katebe, Mwape; Scheithauer, Torsten; Thurmond, Robin L.; Chazot, Paul L.; Ennis, Madeleine
Abstract : The presence of a functional histamine H4 receptor in neutrophils with anti‐inflammatory properties. Abstract : The histamine H4 receptor regulates the inflammatory response. However, it is not known whether this receptor has a functional role in human neutrophils. We found that fMLP (1 μM), but not histamine (0.1–1 μM), induced Mac‐1‐dependent adhesion, polarization, and degranulation (release of lactoferrin). A pretreatment of neutrophils with histamine (0.001–1 μM) or JNJ 28610244 (0.1–10 μM), a specific H4 receptor agonist, led to inhibition of degranulation. Total inhibition of degranulation was obtained with 0.1 μM histamine and 10 μM JNJ 28610244. Furthermore, such inhibition by histamine of degranulation was reversed by JNJ 7777120 and JNJ 28307474, two selective H4 receptor antagonists. However, neither histamine nor the H4 receptor agonist JNJ 28610244 prevented fMLP‐induced, Mac‐1‐dependent adhesion, indicating that the H4 receptor may block signals emanating from Mac‐1‐controlling degranulation. Likewise, engagement of the H4 receptor by the selective agonist JNJ 28610244 blocked Mac‐1‐dependent activation of p38 MAPK, the kinase that controls neutrophil degranulation. We also show expression of the H4 receptor at the mRNA level in ultrapure human neutrophils and myeloid leukemia PLB‐985 cells. We concluded that engagement of this receptor by selective H4 receptor agonists may represent a good, therapeutic approach to accelerate resolution of inflammation.